Assessment of cytokine values in serum by RT-PCR in HIV-1 infected individuals with and without highly active anti-retroviral therapy (HAART) - Meira, D. A. [UNESP]; Almeida, Ricardo Augusto Monteiro de Barros [UNESP]; Barbosa, Alexandre Naime [UNESP]; Souza, Lenice do Rosario de [UNESP]; Olivo, T. E. T. [UNESP]; Henriques, R. M. S. [UNESP]; Golim, Marjorie de Assis [UNESP]; Araujo Jr, J. P. [UNESP]; Nagoshi, L. R. [UNESP]; Orikaza, C. M. [UNESP]; Calvi, Sueli Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2008)
A cross-sectional study was performed on HIV-1 infected individuals with or without antiretroviral treatment (ARV) in the AIDS Day Hospital, Botucatu Medical School, UNESP. Between August 2004 and October 2005, 73 HIV-1 infected individuals were divided into three groups: infected individuals with or without AIDS who had never received ARV (G(1) = 15); patients on HAART that had had plasma HIV-1 RNA viral load (VL) equal to or greater than 50 copies/mL (G(2) = 27); and patients on HAART with undetectable VL for at least the past six months (G(3) = 31). There was also an additional group that comprised blood donors without any sign of the disease and with negative HIV serum tests (G(4) = 20), which was the control group. Serum cytokine levels (values in pg/mL) were measured by enzyme-linked immunosorbent assay (ELISA) and specific mRNA expression by reverse transcription polymerase chain reaction (RT-PCR). Both techniques were performed on the four groups for TNF-alpha, IL-2, INF-gamma, IL-4 and IL-10. All patients were submitted to VL determination and CD4(+) and CD8(+) T lymphocyte counts. The analysis of the results revealed a significant comparison among groups for both methods and an association between the latter (>80% - r(2) > 0.80). There was only one exception, in control individuals for IL-2 by ELISA. The cytokine profiles, in both methods, for the three patient groups, were mature Th-0. The behaviors of IL-2 and INF-gamma required emphasis due to consequent expression of dominant Th profile. Both methods showed low IL-2 and high mean values of INF-gamma in the three groups. Several authors have recently drawn attention to the substantial apoptosis of infected and non-infected CD4(+) T cells, mainly during primary infection, persisting only in those with INF-gamma phenotype producer and not IL-2. HIV infected individuals submitted to HAART are expected to produce IL-2 in an attempt to present Th-1 profile, but in most cases this did not occur.
Keywords: RT-PCR; ELISA; cytokines; HIV; AIDS; HAART; apoptosis